Revolutionizing the AI-Digital Landscape A Guide to Sustainable Emerging Technologies for Marketing Professionals. - Khang, Alex.; Dutta, Pushan Kumar; Gupta, Sachin; Ayedee, Nishu; Chatterjee, Sandeep (Oxford : Productivity Press, 2024)
This book investigates the growing influence of artificial intelligence in the marketing sphere, providing insights into how AI can be harnessed for developing more effective and efficient marketing strategies.
Chapter 21 Detecting Fake News on Social and Collaboration Networks Using Python and Machine Learning -- Chapter 22 The Impact of the Cyber-Physical Environment and Digital Environment on the Socialization Environment -- Chapter 23 Improving Malicious Traffic Detection with the Integration of Deep Neural Networks and Leveraging Hierarchical Attention Mechanism -- Chapter 24 Artificial Intelligence and Tourism: A Bibliometric Analysis of Trends and Gaps -- Index
Description based upon print version of record.
Keywords: Marketing -- Data processing; Artificial intelligence; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Marketing / Direct; BUSINESS & ECONOMICS / Customer Service